Effectiveness of Percutaneous Hypodermic Needle Release of Trigger Finger: A Prospective Study - R Sahaya Jose; M Syed Moosa; SL Binesh (Journal of Orthopedics and Joint Surgery)
Background: Trigger finger, also known as stenosing tenosynovitis, is a common cause of hand pain and dysfunction, with symptoms of pain, swelling, limited finger motion, and triggering sensation. When conservative treatments are not effective, the percutaneous release of the A1 pulley can be performed, which has high clinical outcomes and patient satisfaction with low complication rates. Our aim of the study is to assess the pain and functional outcome following the percutaneous release of the trigger finger by using the visual analog scale (VAS), quick disabilities of the arm, shoulder, and hand (Q-DASH) score, and Quinnell's criteria, respectively, at regular follow-up intervals of 1, 3, 6 months, and 1 year. Material and methods: This is a prospective study conducted between March 2021 and February 2023. A total of 25 patients of both sexes who were not responding to conservative management with trigger-finger were included. Patients with grades III, IV, and V of modified Quinnell's grading were included, and patients who did not respond to conservative management were included in the study. Patients with congenital triggering were excluded. Results: In our present study, the clinical assessment was done by using modified Quinnell grading of trigger finger at the interval of preprocedure, 1, 3, 6 months, and 1 year. Which showed that 21 patients (84%) had excellent results, three patients (12%) had good results, and one patient (4%) had poor results. Only one patient (4%) developed digital nerve injury. Conclusion: Percutaneous hypodermic needle release for the trigger finger is a safe, effective, convenient, and inexpensive day-care procedure without any significant complications in the management of the trigger finger. It is a safe alternative to open surgery. Percutaneous release of the trigger finger has excellent to good results and improves the overall functional outcome. Hence, percutaneous hypodermic needle release can be considered a preferable treatment option for trigger finger.